Aphids presence and temporal distribution (Homóptera: Aphididae) and its parasitoides in cabbage varieties (Brassica olerácea var. capitata L) in the east of La Pampa province, Argentina (Semiárida, 2020)
The aim of the work was to identify the species of plant aphids and his parasitoides and to analyze his population fluctuations in three commercial varieties of cabbage Brassica olerácea L. var. capitata L. We conducted a field trial in the Facultad de Agronomía, UNLPam, located 10 km North of Santa Rosa, La Pampa, to identify aphid species and parasitoids present in three commercial cabbage varieties Brassica olerácea L var. capitata L. and to analyze aphid population fluctuation. Sowing was performed in nursery on 1/02/04. Plants were transplanted, bare root and dry, when they had three or four leaves on 22/03/04. Plants were located 40 cm of each other on line which were separated by 70 cm. The experiment followed a block design (N = 5) with three treatments -varieties- by block. Each variety was assigned at random to one of the three line of each block. Every week we counted 3 leaves in 3 plants, healthy and mummified aphids selected at random from each line and block. Results were compared with ANOVA and tests of Tukey with α = 0.05. The species of aphids detected were Brevicoryne brassicae L. and Myzus persicae Sulz. The Gloria commercial varieties had the lesser amount of aphids. B. brassicae was found parasitized by Diaeretiella rapae (M. Intosh) (Hymenoptera: Braconidae) and this by the hiperparasitoid Alloxysta brassicae (Ashmead) (Hymenoptera: Cynipoidea: Alloxystinae).
Keywords: Cabbage; Aphididae; Parasitoid; Hyperparasitoid